The bilingual approach as a condition for inclusive education for deaf people - Rodríguez-Fleitas, Xiomara (2022)
The recognition of the bilingual approach as a condition for the inclusive education of deaf people, due to the value of linguistic and interlingua contacts in intercultural education, it´s a topic of great social relevance, where sign language is the first language and linguistic basis for learning Spanish. Hence the importance of the intercultural perspective in the training and sociocultural processes that take place in contemporary society, in which communication is essential for the psycholinguistic, sociolinguistic and sociocultural development of deaf people as citizens of law. The application of the Cuban bilingual project demonstrated the potential of deaf people to grow and develop as bilingual-bicultural beings, from the creation of conditions in the educational community in favor of inclusion, which implies the participation of deaf instructors as linguistic models. , sign language interpreters, bilingual teachers, that the family accept the project and participate, the deaf association, the media; expression of a culture of diversity, of the change of mentality to view sign language as a resource and a right of the international deaf community.